Genetic testing before epilepsy surgery – An exploratory survey and case collection from German epilepsy centers. (February 2022) - Boßelmann, Christian Malte; San Antonio-Arce, Victoria; Schulze-Bonhage, Andreas; Fauser, Susanne; Zacher, Pia; Mayer, Thomas; Aparicio, Javier; Albers, Kristina; Cloppenborg, Thomas; Kunz, Wolfram; Surges, Rainer; Syrbe, Steffen; et al.
Highlights: Genetic testing is performed in many German epilepsy centres before epilepsy surgery. Familial syndromes and distinctive phenotypic features should trigger genetic testing. A genetic diagnosis can influence the presurgical decision-making process. mTORopathies tend to have a favourable surgical outcome. Synaptopathies and channelopathies tend to an unfavorable surgical outcome. Abstract: Introduction: Genetic testing in people with epilepsy may support presurgical decision-making. It is currently unclear to what extent epilepsy centres use genetic testing in presurgical evaluation. Methods: We performed an exploratory survey among members of the German Society for Epileptology to study the current practice of genetic testing in presurgical evaluation at the respective sites. Survey participants contributed educational case reports. Results: The majority of participants consider genetic testing to be useful in individuals with familial syndromes or phenotypic features suggesting a genetic etiology. We report 25 cases of individuals with a confirmed genetic diagnosis that have previously undergone epilepsy surgery. Our cases demonstrate that a genetic diagnosis has an impact on both the decision-making process during presurgical evaluation, as well as the postoperative outcome. Conclusion: Genetic testing as part of the presurgical work-up is becoming increasingly established in epilepsy centres across Germany. mTORopathies and genetic hypothalamic hamartomas seem to be associated with a generally favourable surgical outcome. Synaptopathies and channelopathies may be associated with a worse outcome and should be considered on a case-by-case level. Prospective studies are needed to examine the impact of an established genetic diagnosis on postsurgical outcome.